2020
DOI: 10.1039/d0cp04439c
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy challenge of the DFT-based molecular assignment of13C MAS NMR characterization of surface intermediates in zeolite catalysis

Abstract: The influence of the model and method choice on the DFT predicted 13C NMR chemical shifts of zeolite surface methoxide species has been systematically analyzed. Twelve 13C NMR chemical shift...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…We conclude that BASs are crucial for stabilizing the methyl group, away from over-oxidation at the copper-oxo sites. NMR spectroscopic measurements have been used to confirm location of surface methoxy groups at zeolite BASs. , Indeed, work by Kolganov et al and Sushkevich et al clearly indicate that the separated methyl group can be stabilized at BASs. ,, Sushkevich et al concluded that methoxy groups bound to BASs are one of the main products formed over Cu-MOR with an Si/Al ratio of 6. This is close to the ratio of 11 for our model systems.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We conclude that BASs are crucial for stabilizing the methyl group, away from over-oxidation at the copper-oxo sites. NMR spectroscopic measurements have been used to confirm location of surface methoxy groups at zeolite BASs. , Indeed, work by Kolganov et al and Sushkevich et al clearly indicate that the separated methyl group can be stabilized at BASs. ,, Sushkevich et al concluded that methoxy groups bound to BASs are one of the main products formed over Cu-MOR with an Si/Al ratio of 6. This is close to the ratio of 11 for our model systems.…”
Section: Resultsmentioning
confidence: 99%
“…NMR spectroscopic measurements have been used to confirm location of surface methoxy groups at zeolite BASs. 46,47 44,48,49 Sushkevich et al concluded that methoxy groups bound to BASs are one of the main products formed over Cu-MOR with an Si/Al ratio of 6. This is close to the ratio of 11 for our model systems.…”
Section: Methane C−h Activation Bymentioning
confidence: 99%
“…By providing a comprehensive computed data set for various alternative structures and geometries, a goal of establishing a good basis for a more rational assignment of the spectroscopic data is aimed at. 67 We have demonstrated that the local environment affects the stretching frequencies of both adsorbed NO and CO. 28 A decrease in the copper oxidation state, an increase in copper coordination, and a great proximity to the closely located atoms all tend to shift the CO frequency downward. The coordination number and the nature of the coordination environment have distinctive influence on the NO-stretching frequencies in Cu(II), which is in the range from 1850 to 2050 cm −1 .…”
Section: ■ Introductionmentioning
confidence: 86%
“…In a complementary fashion, quantum‐mechanical computations have been used to study the MMC mechanism on these active sites. More recently, the spectroscopic properties of these active sites during MMC have been described with theoretical calculations [31–33] . Most of these computations have used cluster‐model or periodic density functional theory, DFT [34–36] .…”
Section: Introductionmentioning
confidence: 99%